The Relationship between Knowledge and Attitudes towards Smoking Behavior among Students of the Public Health Science Study Program, University of Jambi - Fharin Asroyan; Dwi Noerjoedianto; M. Ridwan; Budi Aswin; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2026)
Smoking remains a significant public health problem in Indonesia, including among university students. Although public health students are knowledgeable about the dangers of smoking, smoking persists. Knowledge and attitudes are important factors that can influence smoking behavior. This study aimed to determine the relationship between knowledge and attitudes and smoking behavior among students in the Public Health Science Study Program at the University of Jambi. This study used a quantitative method with a cross-sectional design. The sample size was 100 respondents selected using simple random sampling. Data were collected through questionnaires and analyzed using the Chi-Square test with a 95% confidence level. The results showed that most respondents had good knowledge and negative attitudes toward smoking. Statistical analysis revealed a significant relationship between knowledge and smoking behavior (p < 0.05) and a significant relationship between attitudes and smoking behavior (p < 0.05). The conclusion of this study is that knowledge and attitudes are significantly related to student smoking behavior. Therefore, interventions in the form of more effective health education and promotion are needed to reduce smoking behavior among university students.